Determination of the camera vision field at aerophotography - Піскунов, О. Г.; Юрчук, І. А.; Білянська, Л. В. (Science-based technologies, 2017)
In this paper an algorithm for determining the field of vision of a camera in aerial photography is presented, which is based on the successive transformation of the translation and rotation of the point at a certain angle around the coordinate axis relative to the origin of the coordinates of some system, software was developed, and its testing was performed, which showed satisfactory accuracy of the calculation . The desktop software version is designed in the form of several classes in the C # language, designed as a dynamically linked library. Library methods allow us to get the coordinates of the angles of the quadrilateral, coordinates of the selected pixel operator, and the images projected onto the plane. In the course of further work, the library classes were rewritten to C ++ and ported into the Linux family of operating systems. Further testing of the library took place on the Raspberry Pi3 Model B. Microplacing (up to 1 km) and small areas of the territory used a rectangular local coordinate system, that is, the curvature of the earth's surface was not taken into account. The estimation of deviation of positioning will be discussed in the following works.